Experimental study of mass transport in PEMFCs: Through plane permeability and molecular diffusivity in GDLs. (10th June 2015) - Mangal, Prafful; Pant, Lalit M.; Carrigy, Nicholas; Dumontier, Mark; Zingan, Valentin; Mitra, Sushanta; Secanell, Marc
Abstract: An experimental study of convective-diffusive transport in polymer electrolyte fuel cell (PEFCs) porous materials is presented. The study is used to estimate through-plane viscous permeability and effective molecular diffusivity of different gas diffusion layers (GDLs). A diffusion bridge based experimental setup is used for molecular diffusivity measurements, with oxygen and nitrogen flowing across the bridge. The pressure difference across the bridge is adjusted to control convective transport. The oxygen transport across porous media is measured using an oxygen sensor, and experimental data is fitted to a combined Fick's and Darcy's model to estimate effective diffusivity. To measure permeability, a variation of the diffusion bridge is used, where a single gas is forced to go through the GDL. The pressure drop across the GDL is measured, and fitted to Darcy's law to estimate viscous permeability. Through-plane permeability and effective molecular diffusivity are measured for several Toray samples with different polytetrafluoroethylene (PTFE) loading. Results show that permeability varies with PTFE loading between 1.13 × 10 −11 - 0.35 × 10 −11  m 2 and diffusibility between 0.209 - 0.071. Increase in the PTFE content in GDLs was found to have an adverse effect on permeability and diffusibility.